Equipment Leasing - Nevitt, Peter K. (Frank Fabozzi, 2000)
Equipment Leasing is a practical reference for financial managers who need background information, and an understanding of how leasing can be utilized as a cost-effective means of equipment financing–especially under the new tax law in the United States. It explores various types of leases, including single investor leases, leveraged leases, tax requirements for true leases’ and lease-buy economic analysis. This invaluable resource includes the background and basics of equipment leasing, history of leasing, synthetic leases, financial reporting of lease transactions by lessees, operating a leasing company, and much more